THE EFFECTIVENESS OF COMMUNITY PARTICIPATION IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN PEMATANG SERAI VILLAGE, LANGKAT - Sebayang, Saimara AM; Lestario, Febrilian; Ritonga, Husni Muharram; Tanjung, Machyani Syafriani Indah (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to analyze the effectiveness of community participation in improving the quality of public services in Pematang Serai Village, Langkat Regency. Based on the results of the study, it was found that community participation in improving the quality of public services in Pematang Serai Village can be said to be effective. This can be seen from several indicators, including: 1) Increasing transparency and accountability of public services, 2) improving the quality of public services and 3) increasing public satisfaction with public services. Factors that support the effectiveness of community participation in improving the quality of public services in Pematang Serai Village include: 1) Community understanding of the importance of participation, 2) village government alignment towards community participation and 3) community togetherness and cohesiveness. Community participation is one of the important factors in improving the quality of public services. With community participation, village governments can better understand community needs and provide higher quality public services.